Feast Your Eyes: An Exploration of Our Consumption of Whales - Liversage, Gwynne (Environmental Humanities, 2024)
In an era where the urgency of climate change is paramount, this research delves into the obscured history of whale consumption and its implications for the South Durban Basin communities. As the global community grapples with the escalating challenge of climate change, proactive measures to bolster resilience are imperative. This study aims to unravel the multifaceted narrative of whale consumption, shedding light on its hidden truths while juxtaposing it against our broader planetary stewardship. Employing a qualitative ethnographic approach, specifically sensory ethnography, this research navigates through the spaces where whales were both physically and visually consumed. Leveraging sensory walks, participant observation, and archival research, the study captures the essence of these spaces, drawing out their historical resonance. Incorporating oral history through informal interviews and merging contemporary photographs with archival imagery enriches the narrative. Interpreting the gathered data filtered into what was made visible or invisible, and then analysed through that lens, the research underscores the scant awareness surrounding the historical significance and ecological impacts of whaling in the South Durban Basin. The findings underscore the interconnectedness of our actions and their repercussions on the environment, revealing the complex web of interactions encompassing reef systems, local communities, and whale migration routes. As the global discourse pivots towards innovative strategies for climate resilience, this research contributes to the ongoing dialogue by deepening our comprehension of human-nature dynamics. By acknowledging our role in shaping ecosystems and influencing climate dynamics, the study accentuates the need for informed decision-making. Armed with this understanding, future strides in climate resilience can be undertaken with prudence, taking into account the fragile equilibrium between human progress and ecological integrity on a global scale.